Wolfgang Iser's "On Translatability": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrik; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces, 1996)
This roundtable discussion of "On Translatability", Wolfgang Iser's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).